Toward Sustainable School Design - Al-Mashaqbeh, Salwa Nayef (مركز البحث وتطوير الموارد البشرية - رماح, 2022)
في الآونة الأخيرة، أصبح مفهوم الاستدامة مصدر اهتمام في العديد من المجالات. هذا المفهوم الشائع هو لتحقيق التنمية المستدامة للمجتمعات. الاستدامة مظلة كبيرة تشمل مفاهيم مختلفة مثل التنمية المستدامة والبيئة المستدامة والمدن المستدامة والعمارة المستدامة. تتضمن العمارة المستدامة استهلاكا منخفضا للطاقة ومرونة عالية وكفاءة عالية في استخدام الموارد لتحسين نوعية الحياة والتنمية المستدامة، من خلال تقليل استهلاك الطاقة وتقليل التلوث البيئي، وتزامن العناصر المكونة لها لتحقيق أهداف التنمية المستدامة. الغرض من هذه الورقة هو اعتماد الاستراتيجيات المبتكرة للتصميم المستدام المرتبطة بمستويات عالية من كفاءة الطاقة والجودة البيئية الداخلية ومعايير الأداء لتعزيز وتحسين البيئة المدرسية لمدرسة طارق بن زياد. ستكون طريقة البحث عبارة عن نهج متعدد الأساليب سيكون مناسبا لتقييم جمع بيانات المدرسة، والذي سيجمع بين استبيان للطلاب والموظفين، ومقابلات مع كل مسؤول؛ لفهم رضاهم العام عن مبنى المدرسة واستخدام برنامج design-builder/ Energy Plus لتقييم محاكاة طاقة مبنى مدرسة طارق بن زياد. All sustainable developments goals come to education. "(Yousafzai,2016) Recently, the sustainability concept has become a common concern in many fields. This widespread concept is, to achieve the sustainable development of societies. sustainability is a big umbrella that includes various concepts such as sustainable development, sustainable environment, sustainable cities, and sustainable architecture. The sustainable architecture includes low energy consumption, high flexibility, and high efficiency in the use of resources to improve the quality of life and sustainable development, while reducing energy consumption and reducing environmental pollution, synchronizes its constituent elements to achieve sustainable development goals. the purpose of this paper is to endorse innovative strategies of sustainable design associated with high levels of energy efficiency, environmental indoor quality, and performance standards to enhance the Tariq bin Ziad school environment. The method of the paper will be a mixed-method approach that will be appropriate to evaluate the school data collection, which will combine a questionnaire survey to students and staff, and interviews with each administrator; to understand their overall satisfaction with the school's built environment and use program design-builder/Energy Plus to assess the Tariq bin Ziad school building energy simulation.
Keywords: التنمية المستدامة -- البيئة التعليمية -- الجودة البيئية -- إرشادات التصميم